Delaying the First Newborn Bath and Exclusive Breastfeeding. Issue 2 (March 2020) - Long, Kathleen; Rondinelli, June; Yim, Ashley; Cariou, Catherine; Valdez, Regina
Abstract: Purpose: The purpose of this study was to determine if changing the timing of the initial newborn bath would have an impact on exclusive breastfeeding during hospitalization. The first newborn bath had been routinely done within 2 hours of age; practice was changed to the first bath being delayed until at least 12 hours of age. A secondary purpose was to examine the nurses' perceived benefits and challenges to such a change. Study Design and Methods: Through a retrospective design, exclusive breastfeeding rates among mother–infant couplets prepractice change (cohort A) were compared with two postchange cohorts (B and C). Cohorts B and C were from the first 5 months and second 5 months, respectively after the practice change. Demographic information, birth type, bath timing, and feeding data were collected. Comparative statistics were applied to the three cohorts to examine differences in exclusive breastfeeding rates. Postpartum nurses were asked two open-ended questions on concerns and benefits of this change via an anonymous survey. Content analysis was completed on responses. Results: There were 1, 463 mother–infant couplets included in three cohorts (A: n = 564; B: n = 468; C: n = 431). There were no significant increases in the exclusive breastfeeding rates (baseline 74.1%) in both the first postimplementation delayed bath cohort (70.1%, p = .207) and the second "sustainability" cohort (79.4%, p = .060). Fifteen of the 60 postpartum nurses completed the survey, for a response rate of 25%. Themes generated from survey responses included concerns (infection control, work distribution), as well as benefits (perceived breastfeeding success, decreased workload) with delaying the first newborn bath. Clinical Implications: Delaying the first newborn bath may be one factor that can influence exclusive breastfeeding rates during postpartum hospitalization. Results have been mixed based on recent literature. In our study, the exclusive breastfeeding rate was already above average, as would be expected in a Baby-Friendly designated hospital and may be a reason we did not see a significant change in the rate among mother–infant couplets in our study. Randomized trials are needed for a rigorous evaluation of timing of the newborn bath and possible link to exclusive breastfeeding in the hospital and beyond. Abstract : Delaying the first newborn bath has been suggested as a strategy to improve exclusive breastfeeding rates during postpartum hospitalization. In this study, exclusive breastfeeding rates were compared before and after a change in practice in newborn bathing in a maternity unit where exclusive breastfeeding rates were higher than average rates in the United States. The practice change was successful and sustained over 10 months, but did not significantly increase the rate of exclusive breastfeeding among the mother-infant cohorts studied.